Individual Features of Vegetative Support for Student-Athletes of Various Specializations - Ivan V. Bocharin; Maxim S. Guryanov; Andrew K. Martuseivch (Journal of Stress Physiology & Biochemistry)
The aim of this paper is assessment of the features of vegetative support of the body of students of various sports specialization.